DESAIN PROGRAM SIMULASI UNJUK KERJA KODE LARGE KASAMI PADA SISTEM KOMUNIKASI DIRECT SQUENCE SPREAD SPECTRUM MELALUI KANAL MULTIPATH FADING - I Ketut Widi Arjana Yasa; Nyoman Pramaita; Ni Made Ary Esta Dewi Wirastuti (Program Studi Teknik Elektro UNUD, 2021)
Selection of Pseudo Noise (PN) code in CDMA multiple access is needed to overcomeproblems related to interference. In this study, we simulate the large kasami code with the aimof knowing the performance of the large kasami code on flat fading channels and frequencyselective fading channels with variations in the number of multipath components. The receiversystem uses a correlation receiver to correlate the code used by each user. The simulationresults from the performance of the large kasami code through the flat fading channel show thatthe simulation carried out is valid, where the simulation BER value is close to the flat theoreticalBER value. The frequency selective fading channel shows different BER values from variationsin the number of multipath components, where the multipath 60 component produces the worstBER value. Auto correlation code large kasami has a value when the time is not equal to zerowhich can interfere with the desired signal and there is a cross-correlation signal level value thatwill interfere with each other's users.